(untitled) (Research, Society and Development, 2021)
Understanding the factors that influence a country’s fiscal performance is imperative to achieve a balanced and sustainable fiscal policy in the long term. Thus, with this work, the proposal is to answer this question by analyzing the impact of institutions and fiscal rules on the primary result for a sample of South American countries. For this purpose, methodological procedures of bibliographic research and the application of an econometric model were used. The result reveals the impact of fiscal institutions and rules, as well as other economic variables and control policies. The conclusion is that fiscal institutions contribute to the achievement of positive primary results, while fiscal rules have no impact on this variable, revealing that for the countries examined here, the path to be followed is to improve their budget process through fiscal institutions.